Service Development Management: A Study of its Applicability in the Minas Gerais State Military Police - De Freitas, Lauro Soares (2010)
The chaotic situation faced by the public safety system in Brazilian states has forced authorities to replace ineffective reactive police strategies with “community preventive actions” to fi ght criminality. However, the military police lacks necessary instruments to develop fast new prevention services that have the quality and effectiveness the community desires. This paper describes how the conceptual-theoretical basis of Service Development Management (SDM) was adapted to the planning of new prevention services in the Minas Gerais Military Police (PMMG - Polícia Militar de Minas Gerais). The work consisted of two interventions: 1) formulating a management pattern for developing preventive services; 2) creating a management instrument for gathering, evaluating, and selecting service ideas, and internal launching of new services. The methodology of action-research was used as the engaging strategy. The conclusion is that transposing the SDM conceptual-theoretical basis from private companies to the PMMG is possible with minor changes which are mostly related to the nature of the corporation. Nevertheless, it must be said that the similarities between principles and characteristics of preventive policing services and those of private companies have made such transposition easier.